Multimedia Interaktif Buku Digital 3D pada Materi IPS Kelas IV Sekolah Dasar - Debi Adis Setiawan; Wahjoedi Wahjoedi; Siti Malikhah Towaf (Graduate School of Universitas Negeri Malang, 2018)
Abstract: This research aims at developing interactive multimedia product that is digital 3D book which is entitled “my home town”. This material is one of the content of social studies and it will be used for students at fourth grade elementary school. The effectiveness of this book is feasible and comply with its validity, attractiveness, effectiveness, and practicality. The development of the product used the model developed by Lee & Owens. The assessment of product validity covered one material expert, one media expert, one teacher, twelve students in small group test, and fifty students in field test. Test product has been trialed in SDN Ngembe 1 Beji, Pasuruan. The obtained result shows that the product produced has met the criteria of validity, attractive, effective, and practical so that the product is feaseble to use.Abstrak: Penelitian ini bertujuan untuk mengembangkan produk multimedia interaktif buku digital 3D tema “Daerah Tempat tinggalku” pada materi IPS untuk kelas IV Sekolah Dasar yang efektivitasnya layak dan memenuhi kriteria kevalidan, kemenarikan, keefektifan, dan kepraktisan. Pengembangan produk menggunakan model yang dikembangkan oleh Lee & Owens. Penilaian kelayakan produk melibatkan 1 ahli materi, 1 ahli media, 1 guru, 12 siswa pada uji kelompok kecil, dan 50 siswa pada uji lapangan. Uji produk dilakukan di SDN Ngembe 1 Beji, Pasuruan. Hasil data yang diperoleh menunjukan produk yang dihasilkan memenuhi kriteria valid, menarik, efektif, dan praktis sehingga produk yang dikembangkan layak untuk digunakan.